A measurement setup for acquiring the local magnetic properties of plastically deformed soft magnetic materials - Bi, Shasha; Sutor, Alexander; Lerch, Reinhard; Xiao, Yunshi (Journal of Applied Physics, 2011)
This paper introduces a new measurement setup for extraction of the local magnetic properties. With the help of finite element method simulations, modifications are made on the previous double-C-yoke method. Small dimension measuring coils are applied in the stray field produced by the magnetic circuit to evaluate the local magnetic properties of the specified part of the specimen. Through the measurements with the plastically deformed materials at different temperatures, it indicates that the magnetic properties of soft magnetic materials are quite sensitive to plastic straining. After high-temperature thermal treatment on the plastically deformed specimen, the local magnetic properties exhibit an obvious recovery. (C) 2011 American Institute of Physics. [doi:10.1063/1.3535549]